COMPOSITIONAL AND PETROGENETIC FEATURES OF SCHISTOSE ROCKS OF IBADAN AREA, SOUTHWESTERN NIGERIA - Oluwatoke O.O.; Adeigbe O.C.; Okunlola O.A. (Earth Sciences Research Journal, 2009)
Amphibole and quartz schist which occur in association with migmatite gneiss, granitic gneiss and Pan African Older Granitebodies around Ibadan area, southwestern Nigeria, were studied with a view to elucidate their compositional characteristics andtheir evolution.Mineralogical determinations from optical studies show a high proportion of granular quartz and accessory muscovite in thequartz schist. The amphibole schist on the other hand comprises mainly dark colored bands of hornblende with subordinate tremolite, chlorite and minor amounts of plagioclase and quartz. Chemical analysis of the samples obtained by Inductively Coupled Plasma Mass Spectrometry (ICPMS) instrumentation method, involving major and trace elements reveal the silicieous nature of the quartz schist and and the amphibole .samples of both rock units are also marked by relatively elevated contents of Ba, Zr, Rb, La and Ce and Zr. In addition, variation plots using Na2O, Al2O,K2Osuggests arenaceous sedimentary ancestry for the quartz schist and an igneous ancestry most probablymafic extrusive volcanics for the amphibole schist. Provenance indicators, such as Ba, in the quartz schists suggest derivation of this sedimentary protolith from the weathering of largely granitic rocks. Similarity of the amphibole schist progenitors with subalkaline basaltic andesite is also implied by the Na2O+K2O versus SiO2 bivariate plot, whilethe Na2O+K2O-Fe2O3 (t)-MgO ternary plot reveal their calc-alkaline affinity. Tectonically, the quartz schists evolved within the passive margin environment, whereas the MgO-Fe2O3-Al2O3 ternary plots reveal an Ocean island basalt tectonic evolution for the amphibole schist.